FARMinta: A sustainable cultivation of black pepper in the province of Cavite - Elaiza Marie R. Denolog, Hazel Ann B. Domacena, Sharmine F. Kho, Aaliyah Mae D. Manansala, Remil A. Micua, Dominique Gabrielle L. Ong Villa, Lhorea Anne H. Reyes 4 0 16; 5
u
Feasibility Study: (BSBA major Business Economics) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2